Recruitment and selection process and the impact of Covid-19 - Pomochshikova, Mariya; Černá, Daniela; Legnerová, Kateřina, 1965-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This thesis focuses on the current situation in the world, which is directly related to the emerging COVID-19 pandemic, as well as its impact on the HR department of a given company and on the recruitment of employees. The bachelor's thesis describes the system of functioning of the personnel department in a company, human resources, recruitment methods and methods, Eichar metrics, a survey conducted with employees and the COVID-19 pandemic. The practical part is focused on the recruiting process in the MSD company, and its main purpose is to show the recruitment process before the pandemic and indicate the consequences of the pandemic, as well as to conduct research that will help to identify the current changes in the company.
Vedoucí práce: Daniela Černá
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses